To BIM or not to BIM: A pilot study on University of Malaya’s architectural students’ software preference - Rosli, M.F.; Razak, A.S.A.; Younus, M.A. (University of Malaya, 2016)
In recent years, Building Information Modelling (BIM) has received enormous attention from the Architectural, Engineering and Construction (AEC) industry around the globe. In 2014, the first Malaysia?s international BIM day was held at Putra World Trade Centre (PWTC) Kuala Lumpur that marked the largest awareness event to highlight the nationwide BIM adoption and implementationpromotion campaign on this new technology. To ensure the success in the implementation, it isimportant for future architectural graduates to be equipped with the operational skill of thesoftware.This, in turn, requires architecture schools in Malaysia to consider adjusting theircurriculums, and syllabus in preparing their students for the demand of the AEC industry. Thisstudy aims to explore and understand the architectural students’ perception towards theadvantage of using BIM software in their design studio projects. An exploratory study has been conducted through a survey among 84 respondents in 3rd, 4th and 5th year of the architectureprogram at the University of Malaya (UM). The result indicates that both AutoCAD and SketchUp are the most commonly used software in both education and practice. In contrast, BIM softwareis found to be less commonly used by the students. This BIMsoftware however does receive positive feedback from the students for its benefits. This could indicate a prospect to embrace BIM technology into UM’s architectural syllabus.